Membedah Hadis Ipar adalah Maut: (Kritik Hadis dan Moralitas Keluarga Muslim) - Abd. Bashir Fatmal; La Ode Ismail Ahmad; Arifuddin Ahmad; Radhie Munadi (Prodi Ilmu Hadis Fakultas Ushuluddin dan Dakwah Universitas Islam Negeri Madura, 2024)
This study is motivated by the complexity of familial relationships in pre-Islamic Arab society and their ongoing transformation in the contemporary era. Interactions between non-mahram family members often lead to potential fitnah and conflict, necessitating a critical examination of the hadith,